The statistical analysis of failure time data - Kalbfleisch, John D; Prentice, Ross L (Wiley-Interscience, 2002)
* Contains additional discussion and examples on left truncation as well as material on more general censoring and truncation patterns. * Introduces the martingale and counting process formulation swil lbe in a new chapter. * Develops multivariate failure time data in a separate chapter and extends the material on Markov and semi Markov formulations. * Presents new examples and applications of data analysis.
Wiley series in probability and statistics
Keywords: statistika, zdravotnická statistika; Analýza statistická; Regrese; Analýza dat